Prevalence of residual inflammatory risk and associated clinical variables in patients with type 2 diabetes. Issue 9 (31st May 2020) - Prattichizzo, Francesco; Giuliani, Angelica; Sabbatinelli, Jacopo; Matacchione, Giulia; Ramini, Deborah; Bonfigli, Anna Rita; Rippo, Maria Rita; de Candia, Paola; Procopio, Antonio Domenico; Olivieri, Fabiola; Ceriello, Antonio
Abstract: Residual inflammatory risk (RIR) is defined as persistent circulating levels of high sensitivity C‐reactive protein (hs‐CRP) >2 mg/L despite an optimal (<70 mg/dL) control of LDL‐cholesterol (LDL‐C) and represents an emerging risk factor for the development of cardiovascular events in patients at high risk of atherosclerosis. Sparse data are available regarding the prevalence of RIR in patients with type 2 diabetes (T2D) and the clinical variables associated with hs‐CRP elevation. Here, we report data from a well‐characterized cohort of patients with T2D (n = 511) stratified for statins use, LDL‐C goal attainment and prevalent T2D complications. Statins use and having at‐target LDL‐C partially affect the number of patients with inflammatory risk when compared with the whole T2D population, with an RIR prevalence of 39.2%. Among the spectra of complications, only patients with nephropathy had a higher prevalence of inflammatory risk. Total cholesterol, non‐HDL‐cholesterol, triglycerides, body mass index and waist‐hip ratio were associated with hs‐CRP, with an increased magnitude in at‐target patients. Conversely, glucose‐related variables were strongly associated with hs‐CRP only in at‐target patients, overall suggesting glycaemic control, insulin resistance, non‐LDL‐C lipid variables and especially central obesity as possible contributors to RIR in patients with T2D and LDL‐C <70 mg/dL.